At-home bleaching: Color alteration, hydrogen peroxide diffusion and cytotoxicity - de Almeida, Leticia Cunha Amaral Gonzaga [UNESP]; Soares, Diana Gabriela [UNESP]; Azevedo, Fernanda Almeida [UNESP]; de Gallinari, Marjorie Oliveira [UNESP]; de Costa, Carlos Alberto Souza [UNESP]; dos Santos, Paulo Henrique [UNESP]; Briso, André Luiz Fraga [UNESP] (FapUNIFESP (SciELO), 2015)
This study evaluated the color change, cytotoxicity and hydrogen peroxide (HP) diffusion caused by different home bleaching protocols: 10% carbamide peroxide (CP) for 3 or 1.5 h, 6% hydrogen peroxide for 1.5 h or 45 min. To quantify the peroxide penetration, disks of bovine teeth were placed in artificial pulp chambers (APCs) containing acetate buffer, which was collected for evaluation in a spectrophotometer. For analysis of cytotoxicity, specimens were adapted in APCs containing culture medium, which subsequently was applied on MDPC-23 odontoblast-like cells for 1 h. Cellular metabolism was evaluated by methyl tetrazolium (MTT) assay and the color change of the specimens was analyzed using the CIE L * a * b * system. The data were submitted to ANOVA and Fisher test (a=5%). The treatment with 10% CP for 3 h was the most effective, and 6% HP for 45 min produced the lowest color change. The groups 10% CP for 1.5 h and 6% HP for 45 min had the lowest trans-enamel dentinal HP penetration, and the 6% HP for 1.5 h had the highest. None of the protocols affected cellular metabolism and morphology. In conclusion, reduced peroxide exposure time reduced the bleaching result; higher HP diffusion did not mean higher effectiveness.
Keywords: Hydrogen peroxide; Odontoblasts; Oxidants/toxicity; Tooth bleaching